AlGaN/GaN pressure sensor with a Wheatstone bridge structure - X. Tan; Y. J. Lv; X. Y. Zhou; Y. G. Wang; X. B. Song; G. D. Gu; P. F. Ji; X. L. Yang; B. Shen; Z. H. Feng; S. J. Cai (AIP Advances, 2018)
In this work, a Wheatstone bridge-type pressure sensor based on AlGaN/GaN heterostructure was fabricated for the first time. The pressure sensor consisted of four gateless high electron mobility transistors (HEMTs) on a 585 μm depth circular membrane, in which 15-μm-thick silicon substrate was left. Direct voltage readout was realized in the AlGaN/GaN pressure sensor, which exhibited a non-linearity of 0.6% with a sensitivity of 1.25 μV/kPa/V over a wide pressure range from 0.1 MPa to 5 MPa. Because of the in-plane isotropic properties, the working mechanism in the AlGaN/GaN pressure sensor is found to be quite different from the silicon-based sensor. Although the resistances of the four gateless HEMTs all increased with enlarging pressure, the changes of neighboring resistors varied with alignments under the piezoelectric effects. Finally, voltage linear readout was realized by the differential operation of Wheatstone bridge circuit.